Energy Purchasing Strategy of Electricity Retailer Considering the Responsibility of Renewable Energy Consumption - Shangwen DAI; Li ZHANG; Ningning LIU; Ming YANG; Chang LIU; Shengnan CAO (Zhongguo dianli)
As one of the major players in electricity trading, the electricity retailer should actively undertake the responsibility of consuming renewable energy. To analyze the influence of the renewable portfolio standard (RPS) on electricity retailers, this paper constructed a new portfolio investment model of energy purchasing. Scenario analysis is performed to describe the uncertainty about the spot price and renewable energy output in electricity markets. The optimal energy purchasing strategy is developed with the minimum transaction cost based on the conditional value-at-risk (CVaR) as the goal, and the punishment mechanism for consumption responsibility examination is introduced to evaluate different examination criteria. The YALMIP toolbox in MATLAB is adopted to solve linear programming in this model. In addition, the influence of risk preference, RPS quotas, renewable-energy forecast accuracy, and the degrees of penalties from regulatory authorities on the optimal energy purchasing strategy of electricity retailers is analyzed by simulation. The results show that the proposed model is effective.